Protein LUMA is a cytoplasmic plaque constituent of various epithelial adherens junctions and composite junctions of myocardial intercalated disks: a unifying finding for cell biology and cardiology - Franke, Werner; Heid, Hans (Cell & tissue research, 2014)
In a series of recent reports, mutations in the gene encoding a protein called LUMA (or TMEM43), widely speculated to be a tetraspan transmembrane protein of the nuclear envelope, have been associated with a specific subtype of cardiomyopathy (arrhythmogenic cardiomyopathies) and cases of sudden death. However, using antibodies of high specificity in immunolocalization experiments, we have discovered that, in mammals, LUMA is a component of zonula adhaerens and punctum adhaerens plaques of diverse epithelia and epithelial cell cultures and is also located in (or in some species associated with) the plaques of composite junctions (CJs) in myocardiac intercalated disks (IDs). In CJs, LUMA often colocalizes with several other CJ marker proteins. In all these cells, LUMA has not been detected in the nuclear envelope. Surprisingly, under certain conditions, similar CJ localizations have also been seen with some antibodies commercially available for some time. The identification of LUMA as a plaque component of myocardiac CJs leads to reconsiderations of the molecular composition and architecture, the development, the functions, and the pathogenic states of CJs and IDs. These findings now also allow the general conclusion that LUMA has to be added to the list of mutations of cardiomyocyte junction proteins that may be involved in cardiomyopathies.
Gesehen am 17.08.2018